2015
DOI: 10.1186/s12889-015-1932-x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria, anaemia and nutritional status among schoolchildren in relation to ecosystems, livelihoods and health systems in Kilosa District in central Tanzania

Abstract: BackgroundMalaria prevalence and transmission intensity in Tanzania is heterogeneous with spatial and temporal variations between geographical areas and ecological systems. The objective of this study was to determine the prevalence of malaria, anaemia and nutritional status in relation to livelihoods, ecosystem and health systems in Kilosa District in central Tanzania.MethodsThis study was conducted in four villages, two characterised by rice irrigation ecosystem and the other two by dry savannah ecosystem an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
2
28
3
1
Order By: Relevance
“…The results of the present study demonstrated a markedly high malaria prevalence compared to other studies performed in different areas of Tanzania [ 3 , 4 ]. For example, a national survey undertaken in different parts of Tanzania reported the general malaria prevalence of less than 10% for most of the regions other than Lake Victoria regions (Mara and Geita) which showed significantly higher malaria prevalences [ 3 ].…”
supporting
confidence: 47%
See 1 more Smart Citation
“…The results of the present study demonstrated a markedly high malaria prevalence compared to other studies performed in different areas of Tanzania [ 3 , 4 ]. For example, a national survey undertaken in different parts of Tanzania reported the general malaria prevalence of less than 10% for most of the regions other than Lake Victoria regions (Mara and Geita) which showed significantly higher malaria prevalences [ 3 ].…”
supporting
confidence: 47%
“…For example, a national survey undertaken in different parts of Tanzania reported the general malaria prevalence of less than 10% for most of the regions other than Lake Victoria regions (Mara and Geita) which showed significantly higher malaria prevalences [ 3 ]. In Kilosa district, central Tanzania, the malaria prevalence of schoolchildren was as low as 4.5% [ 4 ]. However, around the lakeside areas of Lake Victoria malaria prevalence has been reported to be quite high [ 5 , 6 ].…”
mentioning
confidence: 99%
“…The prevalence of malaria parasitaemia among <5 years old children in Morogoro Region (where Kilosa District belongs) has fallen from 15.7% in 2008 to 7.4% in 2012 [ 19 , 20 ]. On the other hand, a recent community-based study in the district indicated a prevalence of 3.5% among schoolchildren; with those from Kimamba having the lowest prevalence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the relationship between food security, malaria and climate change are few [ 9 , 10 ]. Links between agriculture and food security are intuitive, yet understanding of this dynamic is still being developed; meanwhile, studies have only recently begun on the interactions between agriculture and malaria [ 5 , 11 - 13 ]. Though the four drivers are considered separate development issues in need of independent intervention strategies, there are reasons to assume that agriculture, climate change, food security, and malaria overlap and affect each other.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Quando comparada a outros estudos realizados em crianças e adultos com baixas condições econômicas, a prevalência encontrada neste estudo é considerada baixa. (15,17,18) Diante do aumento de casos de anemia e como medidas profiláticas, o Ministério da Saúde adotou a fortificação das farinhas de trigo e milho com ferro e ácido fólico e implementou o Programa Nacional de Suplementação de Ferro, que atende crianças de 6 a 18 meses, gestantes e mulheres no pós-parto. …”
Section: Discussionunclassified